Marine n−3 Fatty Acids and Prevention of Cardiovascular Disease and Cancer - Manson, JoAnn E; Cook, Nancy R; Lee, I-Min; Christen, William; Bassuk, Shari S; Mora, Samia; Gibson, Heike; Albert, Christine M; Gordon, David; Copeland, Trisha; D’Agostino, Denise; Friedenberg, Georgina; et al. (The New England journal of medicine, 2019)
This article reports the n−3 fatty acid portion of a randomized, placebo-controlled, two-by-two factorial trial of vitamin D and marine n−3 fatty acids in the primary prevention of cancer and cardiovascular disease. Fatty acids did not lead to a lower incidence of major cardiovascular events or cancer.